Evaluation of Conflict Management and Its Implications for Employee Productivity at BAPPEDA Langsa City - Kaban, Maju; Nababan, Bernandus; Purba, Bintang Jamudra; Ritonga, Ahmad Fauzi; Siahaan, Samuel Fiktor; Riana, Zenni (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to evaluate conflict management in BAPPEDA Langsa City and its implications for employee productivity. Using a qualitative approach, data was collected through in-depth interviews, observations, and document analysis from 20 employees. The results of the study show that the conflicts that occur are interpersonal and intrapersonal, with a negative impact on employee motivation and mental health. Despite management efforts through open discussions and informal mediation, minimal management support and unclear policies hamper their effectiveness. This study found that conflicts that are not managed properly lead to decreased productivity and increased attendance. The proposed recommendations include increased communication skills training, the development of more concrete conflict management policies, and an encouragement to create a work culture that supports collaboration. This finding is expected to be the basis for BAPPEDA and other government agencies to improve conflict management, thereby creating a more harmonious and productive work environment.